Identifying predation on rodent teeth through structure and composition: A case from Morocco. (August 2015) - Dauphin, Y.; Castillo-Michel, H.; Farre, B.; Mataame, A.; Rbii, K.; Rihane, A.; Stoetzel, E.; Denys, C.
Highlights: Teeth of wild rodents are compared to those extracted from regurgitation pellets. The composition of digested teeth is modified. Modifications differ depending on the bird of prey. These modifications influence the post depositional alterations. Analyses were applied at unidentified predators in Morocco. Abstract: Predation by nocturnal birds of prey is one of the most frequent modes leading to the concentration of rodents in fossil assemblages. This mode of accumulation leaves characteristic surface alterations on bones and teeth. In order to evaluate and characterize the effects of these pre-diagenesis alterations on rodent fossil samples, we have carried out microstructural and chemical analyses on incisors collected from present day Moroccan wild animals and owl pellets. The microstructure of both dentine and enamel was well preserved, but chemical changes were evident in pellet samples and depended on the particular tissue and the nature of the predator. The comparison of compositional data obtained from electron microprobe chemical analyses and infrared spectrometry has allowed us to assign a possible predator to an incisor extracted from a pellet of an unknown origin. This method has further implications for the understanding of taphonomy and palaeoecology of archaeological and fossil sites.